Financial accounting for dummies - Loughran, Maire (--For dummies., 2021)
Learn to speak fluent finance-and ace your exams! Warren Buffett said that "accounting is the language of business." And for many accounting and business students, the obscure terminology of finance makes fluency hard to achieve. Financial Accounting For Dummies can help to demystify abstract concepts in a straightforward, friendly way. With step-by-step examples and real-world scenarios practice, it helps you grasp the fundamentals of finance until you're ready to interpret, analyze, and evaluate corporate financial statements like you've been doing it all your life. Packed with easy-to-understand examples, this book takes you from the big three financial statements all the way through to income taxes. Or join the anti-fraud squad by discovering how to spot the ten most common accounting shenanigans. & grasp introductory financial accounting course material & explore common concepts financial professionals use to compile reports & understand mergers and acquisitions, free cash flow, and statement analysis & know the ten industries with special accounting standards